Kedudukan Hukum Terbitnya E-Rupiah Sebagai Central Bank Digital Currency Ditinjau Dari Undang-Undang Nomor 7 Tahun 2011 Tentang Mata Uang - Saputra, Moh Raka; Hasni, Nadia Nuraini; Astawa, I Ketut; Nurlailasari, Ella (Universitas Sang Bumi Ruwa Jurai, 2024)
This study discusses the legal position of E-Rupiah issuance as a Central Bank Digital Currency (CBDC) in the context of Law Number 7 of 2011 concerning Currency. The development of digital technology has encouraged Bank Indonesia to explore and adopt E-Rupiah as an official form of digital money. In the Law, all transactions in the territory of the Republic of Indonesia must use Rupiah. The issuance of E-Rupiah as a CBDC by Bank Indonesia aims to improve payment system efficiency, support financial system stability, and advance the national digital economy. Legal analysis of E-Rupiah includes a review of its legality, legitimacy, and implementation within the existing legal framework. This includes evaluation of currency regulations, monetary policy, and coordination between Bank Indonesia and other relevant institutions. This research found that the issuance of E-Rupiah must be accompanied by comprehensive implementing regulations